2017
DOI: 10.1016/j.jneb.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Statewide Breastfeeding Hotline Use Among Tennessee WIC Participants

Abstract: The TBH is a resource to address BF concerns, particularly among women who may face barriers to seeking professional lactation advice. Special Supplemental Nutrition Program for Women, Infants, and Children agencies might consider implementing initiatives outside their standard scope of clinic practice to address participants' needs for BF support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…The Department of Health, in accordance with the World Health Organisation, advises that from six months a variety of complementary foods should be introduced alongside continued breastfeeding and/or breast milk substitutes [20,21]. Current parental practices in the UK however deviate from the recommendation in terms of providing a wide selection of appropriate complementary foods, as shown by the latest Diet and Nutrition Survey for Infants and Young Children (DNSIYC) [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Department of Health, in accordance with the World Health Organisation, advises that from six months a variety of complementary foods should be introduced alongside continued breastfeeding and/or breast milk substitutes [20,21]. Current parental practices in the UK however deviate from the recommendation in terms of providing a wide selection of appropriate complementary foods, as shown by the latest Diet and Nutrition Survey for Infants and Young Children (DNSIYC) [22].…”
Section: Introductionmentioning
confidence: 99%
“…13 A study describing a telephonic lactation support program showed that mothers often used the service to clarify breastfeeding-related doubts. 28 All these studies among women in the perinatal period, albeit from high-income country settings, indicate the demand for phone helplines for this vulnerable population. Women with mental health problems who have recently given birth, especially in LAMI countries, may find it difficult to travel to avail timely support.…”
Section: Discussionmentioning
confidence: 99%
“…En relación con los grupos de apoyo para la intervención de problemas asociados a la lactancia materna, es muy frecuente que las madres experimenten dificultades durante la lactancia, y la falta de conocimiento o tener establecidos conceptos errados puede generar sentimientos de frustración, que al no ser mitigados y/o asesorados de la forma correcta pueden causar un efecto desfavorecedor para la LM, conllevando a la reducción en su frecuencia y su duración 59 .…”
Section: Discussionunclassified